Identification and characterization of ribN, a novel family of riboflavin transporters from rhizobium leguminosarum and other proteobacteria - García Angulo, Víctor Antonio (2013)
Rhizobia are symbiotic bacteria able to invade and colonize the roots of legume plants, inducing the formation of nodules, where bacteria reduce atmospheric nitrogen (N2) to ammonia (NH3). Riboflavin availability influences the capacity of rhizobia to survive in the rhizosphere and to colonize roots. In this study, we identified the RL1692 gene of Rhizobium leguminosarum downstream of a flavin mononucleotide (FMN) riboswitch. RL1692 encodes a putative transmembrane permease with two EamA domains. The presence of an FMN riboswitch regulating a transmembrane protein is usually observed in riboflavin transporters, suggesting that RL1692 may be involved in riboflavin uptake. The product of RL1692, which we named RibN, is conserved in members of the alpha-, beta-, and gammaproteobacteria and shares no significant identity with any riboflavin transporter previously identified. In this work, we show that RibN is localized in the membrane cellular fraction and its expression is downregulated by riboflavin. By heterologous expression in a Brucella abortus mutant auxotrophic for riboflavin, we demonstrate that RibN possesses flavin transport activity. Similarly, we also demonstrate that RibN orthologues from Ochrobactrum anthropi and Vibrio cholerae (which lacks the FMN riboswitch) are able to transport riboflavin. An R. leguminosarum ribN null mutant exhibited lower nodule occupancy levels in pea plants during symbiosis assays. Thus, we propose that RibN and its homologues belong to a novel family of riboflavin transporters. This work provides the first experimental description of riboflavin transporters in Gram-negative bacteria.